2021
DOI: 10.1080/23744235.2020.1871066
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the recurrence of SARS-CoV-2 virus: frequency, risk factors, and possible explanations

Abstract: Background Since late 2019, SARS-CoV-2 which leads to coronavirus disease 2019 (COVID-19), has caused thousands of deaths. There are some pieces of evidence that SARS-CoV-2 genome could be re-detectable in recovered patients. Methods We performed a systematic review in the PubMed/Medline database to address the risk of SARS-CoV-2 recurrence. The last update was for 20 November 2020. Among the 1178 initially found articles, 66 met the inclusion criteria and were consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 94 publications
3
38
5
Order By: Relevance
“…In contrast, the rate of recurrence in males was lower than in females. In addition, the result of the systematic review by Piri et al 50 indicates that among all patients that had a recurrence, 47.7% were male, and the others were female. Also, hospital readmission based on sex difference was the same.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the rate of recurrence in males was lower than in females. In addition, the result of the systematic review by Piri et al 50 indicates that among all patients that had a recurrence, 47.7% were male, and the others were female. Also, hospital readmission based on sex difference was the same.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that waning antibodies places individuals at a risk for reinfection, which may explain our finding of the time duration of first infection and reinfection being a mean of 63 days. The presence of antibodies could provide a protective role, but it does not specifically prevent reinfection as supported by findings in a systematic review by Piri et al[102]…”
Section: Discussionmentioning
confidence: 99%
“…However, the previous study did not consider a laboratory criterion of negative results, and the interval between episodes was as short as 28 days from the onset of symptoms; thus, some events may have been second episodes of symptoms and not reinfections. In this sense, there are several publications that use different categories and terms for this phenomenon: reinfection [ 19 , 20 ] recurrence or relapse [ 21 ] and second episode [ 15 ] with precise criteria for each term. Second episodes are those with a second documented SARS-CoV-2 infection and a history of laboratory-confirmed infection but with no negative result between the two episodes, which is required for a case to be considered a reinfection.…”
Section: Discussionmentioning
confidence: 99%
“…However, what is currently controversial is the criterion of temporality between one episode and another. Although relapse occurs in people with less than 45 days between one event and another, despite having presented clinical improvement, Piri defines relapse as testing positive for the virus for more than two weeks and with worsening clinical manifestations [ 21 ]. A meta-analysis of 2568 individuals revealed that interval for recurrence was 35.4 days; however, it has been proposed that recurrence is different from reinfection [ 22 ].…”
Section: Discussionmentioning
confidence: 99%